Newborn screening for severe combined immunodeficiency: Evaluation of a commercial T‐cell receptor excision circle‐based method in Victorian dried blood spots. (1st September 2017) - Richards, Stephanie; Pitt, James; Choo, Sharon
Abstract : Aim: Severe combined immunodeficiency (SCID) is the most severe form of primary immunodeficiency and is fatal in infancy if untreated. As early diagnosis is associated with improved outcomes, SCID is an ideal condition to consider for inclusion in a newborn screening (NBS) programme in Australia. In this feasibility study, we evaluated the EnLite Neonatal TREC kit for detection of T‐cell receptor excision circles (TRECs) from NBS dried blood spots for the identification of known SCID patients in Victoria. Methods: TREC copies/μL were measured retrospectively in 14 children diagnosed with SCID or complete DiGeorge syndrome (CDGS) from 2005 to 2015 at the Royal Children's Hospital, Melbourne. In addition, TREC copies/μL were measured for 501 prospective de‐identified NBS cards. Results: Of 14 known SCID or CDGS samples, 11 were correctly identified as presumptive positive samples with low or undetectable TREC on duplicate testing. The remaining three samples also had low or undetectable TREC on duplicate testing but were considered invalid due to insufficient β‐actin DNA amplification. Of the 501 prospective NBS samples, none were identified as presumptive positive samples on duplicate testing. Conclusions: The EnLite Neonatal TREC kit correctly identified known SCID or CDGS patients as presumptive positive samples, and initial cut‐offs for TREC and β‐actin in the Victorian NBS population were determined. A larger pilot study is required to confirm these proposed cut‐offs and to evaluate the cost and implementation of this screening programme in Victoria, Australia. Overall, this study provides preliminary data to support the introduction of this assay to the NBS programme in Victoria.